European Union : employment issues and external relations. - Ho, Shau Miang. (2011)
Employment policies and issues are concerns that any investor will need to address before making a direct investment in any country. Our project seeks to highlight the employment issues facing the European Union and its possible impact on entrants into the Single European Market. Due to the diversity in cultures and economic development in each Member State, the employment situation is different in each State and even within each State (at local and regional levels); the employment situation can vary.